Vaccine hesitancy and HPV vaccine uptake among male and female youth in Switzerland: a cross-sectional study. Issue 4 (21st April 2022) - Kiener, Laura M; Schwendener, Corina L; Jafflin, Kristen; Meier, Audrey; Reber, Noah; Schärli Maurer, Susanna; Muggli, Franco; Gültekin, Nejla; Huber, Benedikt M; Merten, Sonja; Deml, Michael J; Tarr, Philip E
Abstract : Objectives: Identifying factors associated with human papillomavirus (HPV) vaccine uptake is essential for designing successful vaccination programmes. We aimed to examine the association between vaccine hesitancy (VH) and HPV vaccine uptake among male and female youth in Switzerland. Design: With a cross-sectional study, an interview-based questionnaire was used to collect information on sociodemographic factors, vaccination records and to measure the prevalence of VH using the Youth Attitudes about Vaccines scale (YAV-5), a modified version of the Parent Attitudes about Childhood Vaccinations survey instrument. Setting and participants: Eligible male and female participants, 15–26 years of age, were recruited through physicians' offices and military enlistment in all three language regions of Switzerland. Of 1001 participants, we included 674 participants with a vaccination record available (415 males and 259 females) in this study. Primary and secondary outcome measures: The outcome was uptake for HPV vaccine (having received ≥1 dose of HPV vaccine). Covariates were VH, sex, age and other sociodemographics. Results: 151 (58%) female and 64 (15%) male participants received ≥1 dose of HPV vaccine. 81 (31%) female and 92 (22%) male participants were VH (YAV-5-Score >50). The odds for being unvaccinated were higher for VH women than non-VH women, adjusted OR=4.90 (95% CI 2.53 to 9.50), but similar among VH and non-VH men, OR=1.90 (95% CI 0.84 to 4.31). The odds for being unvaccinated were lower for younger men (born on or after 1 July 2002) than older men (born before 1 July 2002), OR=0.34 (95% CI 0.14 to 0.81), but we found no association between age and vaccine uptake for female youth, OR=0.97 (95% CI 0.48 to 1.97). Conclusions: VH was associated with lower HPV vaccine uptake in female youth but not male youth in our study population in Switzerland. Our findings suggest that issues other than VH contribute to HPV underimmunisation in male youth in Switzerland.